1997
DOI: 10.1007/s004320050078
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of lysosomal cysteine proteases are decreased in renal cell carcinoma compared with normal kidney

Abstract: Renal cell carcinoma contains significantly lower concentrations of the lysosomal cysteine proteases, cathepsins B, C, H, L and S, than does normal kidney, as shown by several methods, such as activity determination, enzyme-linked immunosorbent assay, immunoblotting and immunohistochemistry. The same low levels of enzyme activity and concentration have been determined in renal cell carcinoma metastases in the lung. Our results on the decreased concentration of cysteine peptidases at the protein level would see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Combined elevations of CatB and CatL appear to be common in patients with gastric carcinoma40, 41 and a combination of CatB, CatD, and CatL elevations appear to be common in patients with colorectal and breast carcinoma 42–45. However, reduced activities or immunoreactivities of CatB, CatH, and CatL in neoplasms have been reported: Prostate carcinoma and renal carcinoma tissue display decreased activities and immunoreactivities 26, 27. Other investigators found higher immunoreactivity for CatD in prostate carcinoma,16 suggesting that not all of the lysosomal proteases are regulated similarly and that the decrease or increase of one cathepsin activity or immunoreactivity does not simply reflect an increased number of lysosomes in the cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined elevations of CatB and CatL appear to be common in patients with gastric carcinoma40, 41 and a combination of CatB, CatD, and CatL elevations appear to be common in patients with colorectal and breast carcinoma 42–45. However, reduced activities or immunoreactivities of CatB, CatH, and CatL in neoplasms have been reported: Prostate carcinoma and renal carcinoma tissue display decreased activities and immunoreactivities 26, 27. Other investigators found higher immunoreactivity for CatD in prostate carcinoma,16 suggesting that not all of the lysosomal proteases are regulated similarly and that the decrease or increase of one cathepsin activity or immunoreactivity does not simply reflect an increased number of lysosomes in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of mRNA for CatD, CatH, or CatL have been detected in malignancies of bone, thyroid, breast, colon, and endometrium 22–25. In contrast to these reports, decreased cathepsin activities or immunoreactivities have been found in prostate and renal carcinomas 26, 27…”
mentioning
confidence: 93%
“…For the cathepsin B staining, free‐floating sections were quenched for 20 min in 3% hydrogen peroxide and 10% methanol before pre‐incubation with 5% goat serum in 0.25% Triton X‐100 for 1 h, followed by incubation at 4 °C overnight with rabbit anti‐(rat cathepsin B) antibody (1 : 5000; prepared from rat liver lysosomes, electrophoretically homogeneous, and no cross‐reactivities with other related lysosomal cysteine proteinases, i.e. cathepsin L, S, and H; Kirschke et al. , 1997; Fiebiger et al.…”
Section: Methodsmentioning
confidence: 99%
“…The measurements are often performed with the dipeptide Z-Phe-Arg-Amc as a substrate, which is specific for all papain-like cysteine proteases. Determination of the activity of particular enzymes present in (samples from) cell homogenates or physiological fluids requires the use of complex indirect methods, for instance with the use of specific inhibitors [11,12]. A different, simpler way would be to employ substrates specific for the chosen enzyme.…”
mentioning
confidence: 99%